O processo de redução direta no contexto da descarbonização da siderurgia e a busca por soluções tecnológicas de agentes de recobrimento para pelotas de minério de ferro - Jean Philippe Santos Gherardi de Alencar (2021)
The world steel industry is facing a decarbonization challenge never seen before, which requires technical development and substantial financial expenses. A data survey carried out in the first stage of this work showed that some of the main steel mills in Europe already suffer from a significant deficit between the allowances and verified CO2 emissions. The greater use of the Direct Reduction route like in the HYBRIT and SALCOS projects are some of the highlighted initiatives aiming to avoid such emissions. However, an important aspect for the use of this route is the susceptibility to the clustering that iron ore pellets, which are the main metallic charge used in the reactors, can present. Thus, in the second and third stages of the study, the focus was to discuss this phenomenon that is critical for the Direct Reduction technical operationalization process: the control of pellet clustering. In order to quantify the impacts caused by sticking on the reactor operation, the second part of the work was dedicated to the adaptation of a numerical model that represented a shaft furnace and all the equations of mass, energy and momentum conservation relevant to the process. The peculiarity of this study was that it took into account other physical simulation studies in order to promote equations and parameterizations that would make the model able to simulate this pressure drop due to the cluster’s formation. The selection of the best equation and parameterization was based on an industrial reference value whose burden and Clustering Index were known. Then, the third stage of the study included a large laboratory work plan that aimed to identify which materials and application processes for coating pellets would be more effective in preventing the sticking phenomenon. It was possible to see that the use of Bentonite combined with other refractory materials provided a better Dispersion Degree in the pulps and a lower Clustering Index. Additionally, it was found that the dry application method on the green pellet was ineffective, and this can be explained by the low amount of material on the pellet surface after firing. Among all parameters and tests performed, it was found that the Adhesion Index and the sum of the SiO2, Al2O3, CaO and MgO contents were the most influential in the Clustering Index response variable. The Adhesion Index was also evaluated as a dependent variable, and it was observed that there is a strong relationship between its results and the superficial area measured by N2 adsorption (BET method). Bauxite was the material that performed best in this study, and it can be said that its advantages were the high content of Al2O3 that gave it excellent refractory properties, confirmed by the fusibility test and the high superficial area. Finally, a complementary test step was carried out in order to seek an optimization of the results of the third step and connect these results with the application of the second step model. It was noticed that the application of two coating layers, one in the green pellet and the other in the fired pellet, provided a better Clustering Index results in the two cases evaluated. Furthermore, the use of a thermal treatment technique at 400 °C after the second layer was also beneficial to reduce the Clustering Index. However, the values obtained in these optimizations, although better, were not significantly lower than the reference value of a simple application of Bauxite in a fired pellet. When comparing the impact of these two situations on the numerical model, one with simple Bauxite application and the other with double application and heat treatment, the production gain would be only 0.3 t/h